The Decision Support System In Determining Production Of Packed Cooking Oil At PT. Salim Ivomas Pratama Tbk Using Fuzzy Tsukamoto Method - Muhammad Andre Gunawan Syahputra; Hasanul Fahmi (Putaka Timur Publisher, 2021)
Salim Ivomas Pratama Tbk is a company engaged in processing palm oil into cooking oil packaging. In determining the amount of packaged cooking oil production, it is still manual so that the results are still not optimal, therefore to determine the amount of packaged cooking oil production to meet market demand that fluctuates and does not remain constant from time to time, an alternative is needed that can overcome the problem. One solution to overcome the problem of the amount of production is to use a decision support system with a fuzzy Tsukamoto approach. The author designed a Decision Support System in Determining Cooking Oil Production at PT. Salim Ivomas PratamaTbk Using the Fuzzy Tsukamoto Method. The program used is Visual Basic 2010 and uses Microsoft SQL Server 2008 as the database. With this system, it is expected that PT. Salim Ivomas can easily determine the amount of cooking oil packaging production.